PERANCANGAN E-REPORT FINANCIAL SYSTEM BERBASIS WEB (STUDI KASUS : TOKO KRIPIK BALADO MAHKOTA) - Fanny Oktavia; Yeka Hendriyani (Universitas Negeri Padang, 2020)
The purpose of this article is to contrive the e-report financial system that will be use on kripik balado mahkota store like the sales reporting, purchase reporting, profit and loss, and transaction of sales and purchases from suppliers or buyers. the method of design that will be used in the e-report financial system is using architectural MVC (model, view, and controller)techniques, combined with framework yii2 and PHP, storage media with database tool MySQL, and UML’s model design use case diagram, activity diagram, and class diagram. The results of e-report financial’s design are the electronic report will be available, easily accessible everywhere and every time, also minimize the redundant data and overlap data. So the design of the e-report financial system making the report so easily with the model, method, and supporting media that be used in the system.